2013 Spillover Report : Analytical Underpinnings and Other Background. (Policy Papers; Policy Paper ;, 2013)
High uncertainty in general, and high policy uncertainty more specifically, can have important impact on global investment and output growth. Much of the recent policy uncertainty emanated from the United States and Europe-the world's two largest economies. Spillovers from policy uncertainty can occur through several channels. Trade can be affected if increased policy uncertainty adversely affects economic activity and import demand in the United States and Europe. Policy uncertainty could also raise global risk aversion, resulting in sharp corrections in financial markets and capital outflows from emerging markets. This background note attempts to quantify the impact of U.S. and European policy uncertainty on other regions. Specifically, it addresses the following questions: What do we mean by policy uncertainty? How well can we measure it? How has policy uncertainty in the United States and Europe evolved during the past several decades? And how large are the spillovers to economic activity in other regions? The analysis suggests that sharp increases in U.S. and European policy uncertainty in the past have temporarily lowered investment and output in other regions to varying degrees. It also suggests that a marked decrease in policy uncertainty in the United States and Europe in the near term could help boost global investment and output.